2023
DOI: 10.3390/cancers15041161
|View full text |Cite
|
Sign up to set email alerts
|

Consolidative Radiotherapy for Metastatic Urothelial Bladder Cancer Patients with No Progression and with No More than Five Residual Metastatic Lesions Following First-Line Systemic Therapy: A Retrospective Analysis

Abstract: Local consolidative radiotherapy in the treatment of metastatic malignancies has shown promising results in several types of tumors. The objective of this study was to assess consolidative radiotherapy to the bladder and to residual metastases in metastatic urothelial bladder cancer with no progression following first-line systemic therapy. Materials/methods: Patients who received first-line therapy for the treatment of metastatic urothelial bladder cancer (mUBC) and who were progression-free following treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(34 citation statements)
references
References 54 publications
2
32
0
Order By: Relevance
“…A systematic review and meta-analysis including available reports addressing SBRT in patients with oligometastatic and oligoprogressive urothelial cancer identi ed 6 studies with 158 patients included in total (11). The publications included in the meta-analysis come from small and retrospective studies with signi cant variation regarding inclusion criteria, assessment of outcomes, etc (12)(13)(14)(15)(16)(17), making a comparison between these studies challenging. This meta-analysis showed that most patients were older males with primary tumours in the urinary bladder, in agreement with our data, and as expected for urothelial cancer (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review and meta-analysis including available reports addressing SBRT in patients with oligometastatic and oligoprogressive urothelial cancer identi ed 6 studies with 158 patients included in total (11). The publications included in the meta-analysis come from small and retrospective studies with signi cant variation regarding inclusion criteria, assessment of outcomes, etc (12)(13)(14)(15)(16)(17), making a comparison between these studies challenging. This meta-analysis showed that most patients were older males with primary tumours in the urinary bladder, in agreement with our data, and as expected for urothelial cancer (11).…”
Section: Discussionmentioning
confidence: 99%
“…Only 36% had received palliative systemic treatment before SBRT. Primary metastatic disease, n (%) 5 (13) Palliative systemic treatment pre-SBRT, n (%) 14 (36)…”
Section: Baseline Patient's Characteristicsmentioning
confidence: 99%
“…Aboudaram et al . [36 ▪ ] reported that consolidative radiotherapy to the primary and the metastatic sites (up to five metastases allowed, nonprogressive after induction chemotherapy) was associated both with PFS and OS benefit, with severe RT-related toxicities limited to 2.3%.…”
Section: Role Of Primary Tumour and Metastases Treatment In Synchrono...mentioning
confidence: 99%
“…Specifically for bladder or urothelial cancer, a few retrospective studies (Table 2 ) have reported clinical outcomes with SABR for oligometastases [ 27 32 ]. Lymph nodes were the most commonly treated lesions in these case series [ 27 29 , 31 ]. A retrospective case series of 91 patients with up to 5 metastases reported improved overall survival (HR 0.48, p = 0.026) and progression free survival at 6 months (HR 0.57, p = 0.083) for those who received consolidative radiotherapy to the bladder and residual metastases compared with those in an observation group, with local nodes treated most commonly (64%) [ 29 ].…”
Section: Metastases-directed Radiotherapy For Oligometastatic Bladder...mentioning
confidence: 99%
“…Lymph nodes were the most commonly treated lesions in these case series [ 27 29 , 31 ]. A retrospective case series of 91 patients with up to 5 metastases reported improved overall survival (HR 0.48, p = 0.026) and progression free survival at 6 months (HR 0.57, p = 0.083) for those who received consolidative radiotherapy to the bladder and residual metastases compared with those in an observation group, with local nodes treated most commonly (64%) [ 29 ]. Another multicentre retrospective analysis of 61 patients with ≤ 5 metastases at diagnosis reported on outcomes after SABR to total 82 lesions, commonest being lung (40%) [ 30 ].…”
Section: Metastases-directed Radiotherapy For Oligometastatic Bladder...mentioning
confidence: 99%